Penerapan Model Pembelajaran Inkuiri Untuk Meningkatkan Hasil Belajar Siswa Pada Tema 7 Peristiwa Dalam Kehidupan Di Kelas V SD - Colayana Anjela Simamora; Dewi Anzelina; Dyan Wulan Sari HS; Reflina Sinaga; Ester Julinda Simarmata (Journal on Education, 2023)
In the educational process, the teacher is one of the most important components of other components, such as curriculum goals, methods, facilities and the end of educational goals. The activity and involvement of students as a whole is very important so that learning activities achieve their goals. The existence of optimal student learning activities. Based on observations in class V of SD Negeri 040463 Sumbul, in the learning process the teacher conveys more information by not using learning media so that learning is less interesting. The delivery of learning is done by explaining the material or using the lecture method, giving examples of problems as student exercises. With such a learning process, students are less active and there is no student activity in playing a role. To overcome the above problems, an effective learning approach or learning model is needed and can increase student motivation in the learning process. To improve optimal learning outcomes, applying an inquiry learning model, to renew the student learning process. Based on the analysis and discussion of the results of research conducted in class V SDN 040463 Sumbul Kab, Karo in the 2022/2023 learning year, it can be concluded that the implementation of learning by using the Inquiry learning model on the theme of Events in Life in class V SDN 040463 Sumbul Kab, Karo in the 2022/2023 learning year is categorized as good. it can be seen from the results of students improvement of learning outcome in cycle I obtained 62% of the good category and in cycle II it increased to 88% of the very good category.